Report of labor safety inspector on sanitary and living conditions of factories in Omsk in 1923 - T. V. Glazunova; V. V. Germizeeva (Омский научный вестник: Серия "Общество. История. Современность")
This paper presents an official source that has not been published before describing the problematic aspects of the daily functioning of industry and urban life in Omsk during the period of the new economic policy. The publication is addressed to researchers of the early Soviet society, everyday life, industrial history, sanitary and ecological state of the cities of Western Siberia in the early 1920s